Chiral recognition in amyloid fiber growth. (1st March 2016) - Torbeev, Vladimir; Grogg, Marcel; Ruiz, Jérémy; Boehringer, Régis; Schirer, Alicia; Hellwig, Petra; Jeschke, Gunnar; Hilvert, Donald
Abstract : Insoluble amyloid fibers represent a pathological signature of many human diseases. To treat such diseases, inhibition of amyloid formation has been proposed as a possible therapeutic strategy. d ‐Peptides, which possess high proteolytic stability and lessened immunogenicity, are attractive candidates in this context. However, a molecular understanding of chiral recognition phenomena for d ‐peptides and l ‐amyloids is currently incomplete. Here we report experiments on amyloid growth of individual enantiomers and their mixtures for two distinct polypeptide systems of different length and structural organization: a 44‐residue covalently‐linked dimer derived from a peptide corresponding to the [20–41]‐fragment of human β2‐microglobulin (β2m) and the 99‐residue full‐length protein. For the dimeric [20–41]β2m construct, a combination of electron paramagnetic resonance of nitroxide‐labeled constructs and 13 C‐isotope edited FT‐IR spectroscopy of 13 C‐labeled preparations was used to show that racemic mixtures precipitate as intact homochiral fibers, i.e. undergo spontaneous Pasteur‐like resolution into a mixture of left‐ and right‐handed amyloids. In the case of full‐length β2m, the presence of the mirror‐image d ‐protein affords morphologically distinct amyloids that are composed largely of enantiopure domains. Removal of the l ‐component from hybrid amyloids by proteolytic digestion results in their rapid transformation into characteristic long straight d ‐β2m amyloids. Furthermore, the full‐length d ‐enantiomer of β2m was found to be an efficient inhibitor of l ‐β2m amyloid growth. This observation highlights the potential of longer d ‐polypeptides for future development into inhibitors of amyloid propagation. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Amyloid fibers were grown for a designed dimeric construct based on the [20–41]‐fragment of human β2‐microglobulin and the full‐length 99‐residue β2‐microglobulin in the presence of the corresponding mirror image peptides. We show that the racemic mixture of covalent dimer of [20–41]‐fragment self‐sorts and forms a mechanical mixture of left‐ and right‐handed amyloids. In addition, we demonstrated that d ‐enantiomers act as potent inhibitors of amyloid propagation for the corresponding l ‐peptides.